2016
DOI: 10.3390/en9080641
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Photoanode Design on the Photoelectrochemical Performance of Dye-Sensitized Solar Cells Based on SnO2 Nanocomposite

Abstract: Li-doped ZnO (LZO) aggregated nanoparticles are used as an insulating layer in SnO 2 nanocomposite (SNC) photoanodes to suppress the recombination process in dye-sensitized solar cells (DSSCs). Various weight percentages of SnO 2 nanoparticles (SNPs) and SnO 2 nanoflowers (SNFs) were used to prepare SNC photoanodes. The photocurrent-voltage characteristics showed that the incorporation of an LZO insulating layer in an SNC photoanode increased the conversion efficiency of DSSCs. This was due to an increase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The Φ coll value can be estimated from the lifetime of the electrons injected from the photoexcited dyes, i.e., a longer electron lifetime can enhance the Φ coll value [41]. As presented in Figure 7, we could calculate the electron lifetime (τ) of DSCs with the pristine ZnO/FTO and Ag + (20)-ZnO/FTO electrodes using OCVD measurement results Figure 7a and Equation (1); where k is the Boltzmann constant, T is the temperature, e is the electron charge, and dV oc /dt is the derivative of the V oc transient [42,43]. Much longer electron lifetime was observed in the DSC with Ag + (20)-ZnO/FTO, compared to that of the control cell with the pristine ZnO/FTO electrode, as shown in Figure 7b, indicating that back electron transfer in the DSCs with the Ag + (20)-ZnO/FTO electrode was retarded, and the injected electrons survived in the ZnO conduction band.…”
Section: Influences Of Ag + Deposition On the J Scmentioning
confidence: 99%
“…The Φ coll value can be estimated from the lifetime of the electrons injected from the photoexcited dyes, i.e., a longer electron lifetime can enhance the Φ coll value [41]. As presented in Figure 7, we could calculate the electron lifetime (τ) of DSCs with the pristine ZnO/FTO and Ag + (20)-ZnO/FTO electrodes using OCVD measurement results Figure 7a and Equation (1); where k is the Boltzmann constant, T is the temperature, e is the electron charge, and dV oc /dt is the derivative of the V oc transient [42,43]. Much longer electron lifetime was observed in the DSC with Ag + (20)-ZnO/FTO, compared to that of the control cell with the pristine ZnO/FTO electrode, as shown in Figure 7b, indicating that back electron transfer in the DSCs with the Ag + (20)-ZnO/FTO electrode was retarded, and the injected electrons survived in the ZnO conduction band.…”
Section: Influences Of Ag + Deposition On the J Scmentioning
confidence: 99%
“…When flashing along the core surface, the large current makes the lead between the end shielding screen and the grounding flange disconnected, and then the grounding flange becomes the channel for current conduction, resulting in a more obvious flashover trace from the grounding flange to the high-voltage conductor. One of the important causes of the accident is that the electric field distribution under DC voltage is different from that under AC voltage [5]. Under AC voltage, the electric field distribution depends on the permittivity.…”
Section: Introductionmentioning
confidence: 99%
“…One way to optimize the characteristics is to use a multilayer structure for the photoanode [31]. A multilayer photoanode comprising a dye-loading layer and a light-scattering layer improved the energy conversion efficiency of DSSCs [29][30][31][32][33][34]. Kim et al showed that a multilayer stacked TiO 2 nanoparticle/nanotube photoanode increased the short-circuit photocurrent density by approximately 12.6% [18].…”
Section: Introductionmentioning
confidence: 99%